2019
DOI: 10.1073/pnas.1820990116
|View full text |Cite
|
Sign up to set email alerts
|

SCF FBXO22 targets HDM2 for degradation and modulates breast cancer cell invasion and metastasis

Abstract: Human homolog of mouse double minute 2 (HDM2) is an oncogene frequently overexpressed in cancers with poor prognosis, but mechanisms of controlling its abundance remain elusive. In an unbiased biochemical search, we discovered Skp1-Cullin 1-FBXO22-ROC1 (SCF FBXO22 ) as the most dominating HDM2 E3 ubiquitin ligase from human proteome. The results of protein decay rate analysis, ubiquitination, siRNA-mediated silencing, and coimmunoprecipitation experiments support a hypothesis that FBXO22 targets cellular HDM2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
(78 reference statements)
3
44
0
Order By: Relevance
“…In our current study, we revealed that exogenous overexpression of ROC1 promoted bladder cancer cell proliferation, whereas knockdown of ROC1 expression inhibited tumor growth through induction of the G2/M arrest. Consistent with our current nding and further supporting the importance of CRL in the regulation of tumor cell proliferation, the suppression of the CRL activity using the FBXO22 silencing inhibited cancer progression through targeting of HDM2 for degradation in breast cancer [12]. Mechanistically, DNA damage is the most common cause to induce cell G2/M arrest [18].…”
Section: Dysregulation Of Cell Proliferation Is a Landmark During Tumsupporting
confidence: 89%
See 1 more Smart Citation
“…In our current study, we revealed that exogenous overexpression of ROC1 promoted bladder cancer cell proliferation, whereas knockdown of ROC1 expression inhibited tumor growth through induction of the G2/M arrest. Consistent with our current nding and further supporting the importance of CRL in the regulation of tumor cell proliferation, the suppression of the CRL activity using the FBXO22 silencing inhibited cancer progression through targeting of HDM2 for degradation in breast cancer [12]. Mechanistically, DNA damage is the most common cause to induce cell G2/M arrest [18].…”
Section: Dysregulation Of Cell Proliferation Is a Landmark During Tumsupporting
confidence: 89%
“…ROC1 contains a small zinc-binding domain (the RING nger), which is evolutionarily conserved and is essential in embryonic development, while aberrant ROC1 expression led to CRL dysfunction and embryonic lethality [7,8]. ROC1 is also essential in maintenance of the genome integrity and cancer development [8][9][10][11][12]. Our previous studies demonstrated that ROC1 protein was overexpressed in bladder cancer tissues, while knockdown of ROC1 expression reduced the CRL activity, triggered accumulation of its speci c substrates (such as p21, p27, and DEPTOR), leading to suppression of tumor progression [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, FBXO22 was reported to ubiquitylate SNAIL for degradation. This degradation was dependent on the phosphorylation of SNAIL by GSK3β 8,59 . In agreement with GSK3β as a negative regulator of EMT, activation of Wnt signaling by suppression of GSK3β, is known to induce EMT 60 …”
Section: Fbxo22 Regulates Cancer Metastasesmentioning
confidence: 69%
“…Zhu XN et al [29] nding show that FBXO22 is highly expressed in human lung cancer at the protein level. Bai J et al [30] reveal that SCF-FBXO22 targets HDM2 for degradation and possesses inhibitory effects against breast cancer tumor cell invasion and metastasis. We also found the increased FBXO22 expression in oligodendroglial tumor samples and proved its prognostic value for cancer patients.…”
Section: Discussionmentioning
confidence: 99%